Post-pandemic depression, anxiety, and stress: A look at the mental health of medical and administrative staff - Pacheco-Flores Laura Iraís; Pineda-Téllez Magno Edén; Ramos-Tovar Erika (Acta Psychologica)
Introduction: Research has shown how mental health among hospital staff worldwide was affected during the COVID-19 pandemic. However, evidence of the physiological status of healthcare and administrative workers at the first level of medical care post-pandemic is scant. Therefore, it is necessary to identify mental health problems among hospital staff following the COVID-19 pandemic. Objective: To determine the prevalence of symptoms and severity of depression, anxiety, and stress among health personnel in the primary care post-pandemic of the Institute of Social Security and Services for State Workers in Puebla. Materials and methods: A cross-sectional observational study was conducted on medical and administrative staff, comprising 190 participants who worked during the pandemic. A data collection instrument and the 21 item Depression, Anxiety, and Stress Scale were used to determine the prevalence of symptoms and severity of these three mental health issues. Results: The prevalence of symptoms of depression was 20.5 %, with a moderate predominant severity index (38.5 %), anxiety was 33.2 %, with an extremely severe predominant index (36.5 %), and stress was 30.0 %, with a moderate predominant severity index (36.8 %), respectively. The nursing subgroup, within the medical area staff, exhibited a prevalence of anxiety symptoms of 44.7 %, which was statistically significant (p = 0.008). Conclusion: Despite the post-pandemic period during which this study was conducted, the nursing staff was the most affected group in terms of the prevalence of symptoms of anxiety and depression. Another relevant finding was that administrative workers showed an extremely severe intensity of symptoms of depression, anxiety, and stress.